2006
DOI: 10.1016/j.ejheart.2005.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of right ventricular lead position in cardiac resynchronisation therapy☆

Abstract: Background: The benefit of biventricular pacing (BiV) may be substantially affected by optimal lead placement. Aim: To evaluate the importance of right ventricular (RV) lead positioning on clinical outcome of BiV. Methods and results: A total of 99 patients with symptomatic heart failure and implantation of BiV system were included. Position of the left-ventricular (LV) lead was selected based on timing of local endocardial signal within the terminal portion of the QRS complex. RV lead was preferably positione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 23 publications
2
26
1
2
Order By: Relevance
“…Some studies corroborate the results presented 9,10 . Right ventricular (RV) lead implantation in the RV outflow tract was performed in three patients of the BV group, aiming at optimizing the ventricular resynchronization, a technique that is supported by some authors 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies corroborate the results presented 9,10 . Right ventricular (RV) lead implantation in the RV outflow tract was performed in three patients of the BV group, aiming at optimizing the ventricular resynchronization, a technique that is supported by some authors 25 .…”
Section: Discussionmentioning
confidence: 99%
“…24 In their study, the implantation of the RV leads was guided by measuring intervals between RV and LV electrograms. Because the methods used in our study for determining the RV pacing site were similar to those of Lucie et al, we expect that LV end-diastolic diameter as a sign of LV reverse remodeling will show a more significant reduction in response to BVP using the RV midseptum than to BVP positioned in the RVA.…”
Section: Hemodynamic Assessment Of the Rvot And Rv Mid-septummentioning
confidence: 99%
“…50 Several small studies have shown conflicting results regarding the effect of RV lead position (RV midseptal position versus RV apex) in CRT. 51,52 CARDIAC RESYNCHRONIZATION FOR THE FAILING RIGHT VENTRICLE There is preliminary evidence that resynchronization therapy may be beneficial for RV failure in the setting of increased afterload. Studies to date have been focused on animal models of pulmonary arterial hypertension and on patients with congenital heart disease and chronic thromboembolic pulmonary hypertension.…”
Section: Cardiac Resynchronization For Left Ventricular Failurementioning
confidence: 99%
“…Exactly why some patients do not respond to CRT is not completely understood; however, evidence suggests that baseline RV function and, potentially, the location of RV pacing play important roles in responsiveness to CRT. [50][51][52] Poor baseline right ventricular function as assessed by TAPSE has been shown to correlate to reduction in LV end-systolic volume following initiation of CRT, indicating baseline RV function is a relevant predictor of CRT response. 50 Several small studies have shown conflicting results regarding the effect of RV lead position (RV midseptal position versus RV apex) in CRT.…”
Section: Cardiac Resynchronization For Left Ventricular Failurementioning
confidence: 99%